Exploring provocation as a research method in the social sciences. Issue 2 (4th March 2017) - Pangrazio, Luci
Abstract: This paper explores provocation as an approach towards social science research. While routinely used in natural science and arts research, this paper argues provocation might enable the social science researcher to initiate critical reflection amongst participants on issues that are often otherwise overlooked, obscured or accepted as naturalised practice. By assuming the role of provocateur, stimulator and/or agitator, the social science researcher can interrupt the flow of everyday life in order to illuminate and draw attention to complex social issues. Using research interventions that embrace, rather than deny, the socially constructed nature of the research process, provocation provides an alternative to largely non-obtrusive methods favoured in much social science research. This paper concludes by outlining the practical and methodological issues associated with this approach – in particular the complicated ethics of provoking reflection on topics that might not have otherwise come to the participant's attention.